Effects of biological additives on silage composition of Mott dwarf elephantgrass and animal performance - Clavero, Tyrone; Razz, Rosa (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
This experiment was conducted to study the effects of cellulose enzymes and lactic acid bacteria on the fermentation characteristics, chemical composition, nutritive value and animal performance of Pennisetum purpureum cv. Mott silage. Five kinds of preparation were made: sugar molasses (control), sugar molasses and cellulase enzymes, cellulase enzymes, concentrate of lactic acid bacteria and sugar molasses and concentrate of lactic acid bacteria. Significant differences (P < 0.05) were found in fermentation quality and chemical composition between control and the biological additives treated silage. Addition of cellulase enzymes and lactic acid bacteria resulted in decreased of pH value, cell wall content and increased lactic acid concentration. The biological additives increased silage intake and live weight by growing steers.